2021
DOI: 10.3389/fmed.2021.707242
|View full text |Cite
|
Sign up to set email alerts
|

Post-keratoplasty Infectious Keratitis: Epidemiology, Risk Factors, Management, and Outcomes

Abstract: Post-keratoplasty infectious keratitis (PKIK) represents a unique clinical entity that often poses significant diagnostic and therapeutic challenges. It carries a high risk of serious complications such as graft rejection and failure, and less commonly endophthalmitis. Topical corticosteroids are often required to reduce the risk of graft rejection but their use in PKIK may act as a double-edged sword, particularly in fungal infection. The increased uptake in lamellar keratoplasty in the recent years has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 157 publications
1
35
0
1
Order By: Relevance
“…In addition, contact lens wear has been shown to be more commonly implicated in filamentous FK than yeast FK, which was demonstrated by our study and other studies [24,30]. On the other hand, yeast infections, particularly Candida spp., were commonly observed in eyes with ocular surface diseases, previous history of corneal transplantation and use of topical corticosteroids [24,30,35]. We similarly observed that yeast was more commonly associated with prior corneal surgery and the use of topical corticosteroids, though not statistically significant, likely due to a type II error as a result of low sample size.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, contact lens wear has been shown to be more commonly implicated in filamentous FK than yeast FK, which was demonstrated by our study and other studies [24,30]. On the other hand, yeast infections, particularly Candida spp., were commonly observed in eyes with ocular surface diseases, previous history of corneal transplantation and use of topical corticosteroids [24,30,35]. We similarly observed that yeast was more commonly associated with prior corneal surgery and the use of topical corticosteroids, though not statistically significant, likely due to a type II error as a result of low sample size.…”
Section: Discussionsupporting
confidence: 54%
“…We similarly observed that yeast was more commonly associated with prior corneal surgery and the use of topical corticosteroids, though not statistically significant, likely due to a type II error as a result of low sample size. With the shifting trend in penetrating keratoplasty to lamellar keratoplasty, interface infectious keratitis, including Candida-related infection following endothelial keratoplasty, has become increasingly common in the clinic and poses significant diagnostic and therapeutic challenges [35][36][37]. Therefore, knowledge of the risk factors can provide useful clues to the underlying causative organisms, potentially guiding the choice of antifungal treatment, especially in culture-negative FK cases.…”
Section: Discussionmentioning
confidence: 99%
“…Keratitis is a leading cause of visual impairment and blindness. Due to increased contact lens use or corneal surgery, the incidence of keratitis has been increasing in recent years [ 88 , 89 ]. Although nanocarrier-based delivery systems can eliminate or control the infection, some problems including non-specific and uncontrolled release still exist.…”
Section: The Classification Of Bioinspired Nanostructured Systemsmentioning
confidence: 99%
“…Slit-lamp examination shows the presence of corneal infiltrate which can be scraped and sent for microbiological analysis for the diagnosis [ 18 ]. Topical antibiotics are the mainstay of therapy especially in early cases but severe or recalcitrant infections may require systemic medications and in severe cases may also require surgical intervention with a therapeutic keratoplasty [ 19 ]. The choice of antibiotic depends on the suspected causative organisms and their sensitivity pattern.…”
Section: Clinical Presentation Of Keratitis and Conjunctivitis And Tr...mentioning
confidence: 99%